Predicting Rural Women's Breast Cancer Screening Intention in China: A PLS-SEM Approach Based on the Theory of Planned Behavior - Sun, Yanjun; Yuan, Jiawei; Liu, Wuqianhui; Qin, Banghui; Hu, Zhiqing; Li, Jianwei; He, Yuan (Frontiers in Public Health, 2022)
Background: It was reported that the incidence of Breast cancer (BC) was highest among the cancers worldwide. Breast cancer screening (BCS) program is regarded as an effective preventive measure. However, rural women’s willingness to participate in BCS program is reported to be low. In order to provide measures to prevent the BC,it is necessary for the government to identify the influencing factors of rural women’ BCS intention. Methods: A cross-sectional study was conducted among 3011 rural women by a stratified sample method through face-to-face interviews on a self-designed questionnaire based on the theory of planned behavior (TPB). The partial least square structural equation model (PLS-SEM) was conducted to determine the predictors of BCS intention and a multi-group analysis (MGA) of age was performed to identify if there were differences in all hypotheses between different age groups. Results: There were still rural women who had never accepted BCS within 5 years (41.7%) .Research model of rural women’s intention to accept this prevention against BC was rational. All of the hypotheses are supported. Especially, subjective norm (SN) (=0.345, p＜0.001) is found to be the strongest predictor followed by the perceived behavioral control 1 (PBC 1) (personal factors including distance, transportation, busyness, et al.) (=0.165, p＜0.001), attitude(=0.152, p＜0.001), past behavior (PB) (=0.150, p＜0.001), knowledge(=0.121, p＜0.001) and perceived behavioral control 2 (PBC 2) (pain and cultural-social factors including embarrassment from physician, et al.) (=0.042, p＜0.05). Advocacy and education (A&E) and the medical level and service attitude (ML&SA) of township health centers and village clinics can affect BI through attitude, SN, PBC. The results of MGA of age indicate that there are significant differences among rural women with different ages in regard to the relationship between A&E and PBC2 (p＜0.01) and the effect of PB on BI (p＜0.001). Conclusions: The TPB with the addition of PB, Knowledge, ML&SA and A&E is a theoretical basis for the implementation of intervention measures to enhance the rural women’s BCS willing. MGA of age is conducive to promoting the implementation of the BCS policy. The findings are of great significance to improve rural women’s health level.